Motion Graphic untuk Pengenalan Warna Dalam Bahasa Inggris - Arta Uly Siahaan; Heny Anggraini Putri; Afdhol Dzikri (Politeknik Negeri Batam, 2021)
One of the levels of education for early childhood is Kindergarten. The presence and development of technology has a considerable influence on the development of learning media that utilizes video-based media. The use of video as a medium for learning color recognition in English in Kindergarten is expected to enhance childrens’ understanding. The aim of this research was to develop learning media to recognize colors in English through the implementation of motion graphics and to convey material about color in English through learning media in the form of motion graphics that have been made. This product was developed using the Luther Sutopo method and distributed to Ibn Khaldun's Islamic Kindergarten. Previously, a test was conducted where it was found that this media was very good to use and it was proven that the students' average score had increased by learning to use this media.